The Evolution of Radio Broadcasters' Roles in the Dynamic Digital Media Landscape - Wahyuanto, Eko; Dian Wardiana Sjuchro; Harlita Nindhasari; Harliantara (Jurnal Pewarta Indonesia, 2025)
The advent of the digital era has precipitated substantial challenges and opportunities for radio broadcasters to navigate the evolving digital media landscape. This study undertakes a comprehensive analysis of the evolution of radio broadcasters' roles in response to the intense competition from digital media platforms. Utilising a qualitative research methodology, this study employs a comprehensive approach that incorporates literature review, observational studies, and document analysis. It examines the transformative impact of digital technology on the operational dynamics of radio broadcasters, novel challenges and opportunities they encounter, and strategic measures they employ to maintain relevance and attract listeners. These findings indicate that successful radio broadcasters employ digital technology to extend their reach, cultivate robust listener communities, and facilitate customised listening experiences. These broadcasters have adopted digital platforms including online streaming, podcasts, and social media to interact with their audiences. Concurrently, radio broadcasters are acquiring new competencies in digital content production, data analytics, and multimedia to adapt to evolving media landscapes. Nevertheless, challenges persist, including intensified competition, fragmented audiences, and the need for sustainable digital business models. To thrive in the digital era, radio broadcasters must adopt audience-centric strategies, create unique and engaging content, and innovate continuously. The findings of this study contribute to the theoretical and practical understanding of the evolving roles of radio broadcasters, and provide insights for the future development of the radio broadcasting industry in the digital age.